2022
DOI: 10.3390/ph15101271
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Cancer Effects of Mitochondrial-Targeted Triphenylphosphonium–Resveratrol Conjugate on Breast Cancer Cells

Abstract: Breast cancer is the most commonly diagnosed cancer in women. Resveratrol, a naturally occurring phytochemical, shows great promise in developing novel anti-cancer therapies. This study hypothesized that the mitochondria-targeted delivery of resveratrol would increase its potency and induce mitochondria-mediated apoptosis. The targeted delivery of resveratrol was achieved by conjugating resveratrol to triphenylphosphonium (TPP). The anti-cancer effects of TPP-resveratrol were studied in the murine breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In recent years, resveratrol has gained signi cant attention from scholars both domestically and internationally due to its effective anti-tumor activity. Resveratrol has been found to inhibit breast cancer both in vivo and in vitro, and its mechanism of action is closely related to various molecular targets including cell proliferation, epithelial-mesenchymal transition, chemosensitization, invasion and metastasis, apoptosis, and epigenetics [24,25]. Numerous preclinical experiments have demonstrated that resveratrol inhibits the expression of histone transferase EZH2 by regulating the dephosphorylation of protein kinase ERK1/2, resulting in the inhibition of growth and proliferation of breast cancer cells [26].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, resveratrol has gained signi cant attention from scholars both domestically and internationally due to its effective anti-tumor activity. Resveratrol has been found to inhibit breast cancer both in vivo and in vitro, and its mechanism of action is closely related to various molecular targets including cell proliferation, epithelial-mesenchymal transition, chemosensitization, invasion and metastasis, apoptosis, and epigenetics [24,25]. Numerous preclinical experiments have demonstrated that resveratrol inhibits the expression of histone transferase EZH2 by regulating the dephosphorylation of protein kinase ERK1/2, resulting in the inhibition of growth and proliferation of breast cancer cells [26].…”
Section: Discussionmentioning
confidence: 99%
“…Triphenylphosphine (TPP), a non-localized cationic group composed of three benzene rings, is commonly used to mediate chemotherapeutic drugs or nano-preparations to overcome the obstruction of biomembranes and, subsequently, target mitochondria [20,184,185].…”
Section: Triphenylphosphine Modified Nanocarriermentioning
confidence: 99%